Petrochronology of ultrahigh-temperature migmatites from the Arapiraca Complex, Borborema Province, NE Brazil - Tesser, Lucas Ramos (2021)
This work reports on the first finding of sapphirine-bearing ultrahigh-temperature (UHT) metamorphic rocks within the Borborema Province, in NE Brazil. The investigated UHT diatexites outcrop in the Arapiraca Complex, a high-grade Paleoproterozoic block embedded within the Neoproterozoic metavolcano-sedimentary sequence of the Sergipano fold-and-thrust belt. A sapphirine-bearing diatexite sample preserves two distinct residual mineral associations as inclusions in cordierite poikiloblasts: a volumetrically dominant silica-saturated, garnet-sillimanite-orthopyroxene-quartz domain, and a restricted silica-undersaturated, sapphirine-magnetite-spinel-corundum domain. Phase equilibrium modeling for the whole-rock bulk composition constrained the reactions preserved in the silica-saturated domain, which coupled with reintegrated ternary feldspar thermometry, Al-in-orthopyroxene thermobarometry, indicates peak UHT metamorphism occurred at ~970 oC/8.5 kbar followed by a clockwise near isobaric cooling stage crossing the H2O-undersaturated solidus at ~900 oC/7.7 kbar. The T-MSiO2 and P-T phase equilibrium modeling reveals that the stabilization of the first magnetite-spinel in the silica-undersaturated domain can be a product of domainal SiO2-depletion ascribed to inherited compositional banding and progressive melt loss episodes. The appearance of sapphirine as thin coronas around previously formed magnetite-spinel cores requires an increase in silica-activity during retrogression. This was driven by chemical interaction between the silicaundersaturated domain and trapped silica-rich leucosomes. U-Pb dating of zircons coupled with trace elements chemistry allows constraining the timing of melt crystallization between c. 2.03 and 1.96 Ga, following the peak of UHT metamorphism and supporting a protracted, c. 70 My period of melt presence in the crust. The UHT metamorphism in the Arapiraca Complex is related to a contemporaneous UHT event recorded within the São Francisco Craton, and more broadly coincides with high geothermal gradients at c. 2.0 Ga linked to the formation of the Columbia supercontinent. The integration of new petrological and geochronological data indicates that the Arapiraca Complex is a continental ribbon pulled away from the São Francisco-Congo paleocontinent possibly during the early Neoproterozoic Cariris Velho rifting event and opening of the Sergipano basin between c. .98-0.75 Ga. During the late Neoproterozoic at c. 0.63-0.57 Ga, the Arapiraca Complex continental ribbon thrusted back onto the northern margin of the São Francisco Craton as an inlier of the Sergipano fold-and-thrust belt.